Strain determination in heterostructures by TEM in selected area electron diffraction mode. (December 2020) - Snigirev, L A; Kirilenko, D A; Bert, N A
Abstract: The technique for determination of strain and elemental composition distribution across the graded layer in heterostructures by means of selected area electron diffraction in transmission electron microscope (TEM) is proposed. The approach accounts for the modification in the residual elastic strain due to sample thinning during TEM specimen preparation. The technique is approved using In0, 7 Ga0, 3 As/Inx Al1-x As/GaAs (001) and Al0, 75 Ga0, 25 N/AlN/Al2 O3 heterostructures, and the results are in a good agreement with those obtained by alternative ways.